Stare decisis and ratio decidendi - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
The maxim stare decisis et non quieta movere literally means ‘to stand by the decision, and not to disturb the settled matters’ i.e. to stick with what has been decided or the like cases should be decided alike. The commonly used term is the doctrine of stare decisis or the rule of judicial precedent which dictates that it is necessary for each lower tier to accept loyally the decision of the higher tiers. Thus, a court other than the highest court is obliged generally to follow the decision of the court at a higher or the same level in the court structure subject to certain exceptions. The application of the doctrine from a higher court to a lower court is called the vertical stare decisis